Improving Business Productivity Performance through Entrepreneurship Training and Entrepreneurial Self-Efficacy - Nanang Adie Setyawan; Bagus Yunianto Wibowo (Jurnal Ekuilnomi, 2023)
This study was conducted to identify entrepreneurial desire and entrepreneurial productivity among Semarang State Polytechnic students after post-COVID-19. Respondents in this study were 100 Semarang State Polytechnic students who own businesses. This study utilized confirmatory factor analysis and maximum likelihood estimation in SEM (Structural Equation Modeling) using AMOS 24.0 statistical software. Data collection was performed using questionnaires with various semantic scales. The results of parameter estimation align with the hypothesis: entrepreneurial knowledge significantly affects business preference, with a normalized coefficient estimate of 0.586 and a P-Value of ***, entrepreneurial training positively impacts business preference with a normalized coefficient estimate of 0.470 and a P-Value of ***, and entrepreneurial interest significantly affects business productivity with a normalized coefficient estimate of 1.007 and a P-Value of ***. The study concludes that, in the current post-COVID-19 context, students involved in startups need to enhance their education and understanding of entrepreneurship. Innovation is essential for survival and growth in a rapidly changing environment.